REVISITING EARLY CHILDHOOD ISLAMIC EDUCATION LEADERSHIP THROUGH MARIA MONTESSORI'S VISION OF AN INCLUSIVE AND PREPARED ENVIRONMENT - Yunjiati, Dewi; Prasanti, Aulia Eka; Khansa, Sabrina Anindya; Saputra, Tegar Filah; Siswadi (STKIP Subang, 2026)
This article aims to reconstruct the concept of leadership in Early Childhood Islamic Education (ECIE) through a philosophical reading of the concept of the prepared environment developed by Maria Montessori. Until now, ECIE leadership has tended to be understood within an administrative and managerial framework, often disconnected from the pedagogical experiences of children. This approach has limited the implementation of inclusivity, which often stops at the policy level rather than actual practice in the learning environment. This research uses a qualitative approach based on literature review with philosophical and hermeneutic analysis of key Montessori literature, inclusive leadership theory, and Islamic education studies. Data were analyzed through a process of concept reduction, thematic categorization, and reflective synthesis to develop a new conceptual framework. The study's primary focus lies in the shift in leadership paradigm from authority to design of learning environments. The results show that the concept of the prepared environment offers a strong theoretical basis for understanding leadership as a design practice that directly shapes children's learning experiences. The environment is positioned as an active medium that enables the realization of inclusivity in a concrete, rather than merely normative, manner. In the context of ECIE in Indonesia, this approach has the potential to be integrated with Islamic educational values, despite facing cultural, structural, and resource challenges. This article contributes to the development of Islamic educational leadership theory by emphasizing the importance of environmental design as a core practice of contextual and reflective inclusive leadership.